The Influence of Bank Health Level with RGEC and Methods Market Share on Liquidity Level (Study on State-Owned Banks Listed on the IDX for the Period 2012-2020) - Sirait, Hermin; Citarayani, Irma; Saminem, Saminem; Pujiastuti, Endang Tri (Budapest International Research and Critics University, 2021)
This study aims to determine how the influence of the financial soundness of banks based on the RGEC (Risk Profile, Good Corporate Governance, Earnings and Capital aspects) method and Market Share, on the level of liquidity in state-owned banks listed on the IDX for the period 2012 to 2020. This study was carried out by processing secondary data, the analysis technique used multiple linear regression. The results of this study indicate that the financial soundness of banks using the RGEC method has no effect on liquidity, and the market share of both Loan market share and Deposit Market share has a negative effect on liquidity. The effect of financial soundness of banks and market share only affects about 30% of the Loan to Deposit Ratio, and about 70% is influenced by other factors.